Reproductive Profile of Black Soldier Fly (Hermetia Illucens L.) on Different Rearing Substrates as Ruminant Feed - Aulia Puspita Anugra Yekti; Nurul Isnaini; Sri Wahjuningsih; Ardyah Ramadhina Irsanti Putri; Hanief Eko Sulistyo (Jurnal Ilmu-Ilmu Peternakan, 2023)
There is lack of evidence on the black soldier fly (Hermetia Illucens L.) and its use as a biological control and waste recycle agent. Unknown information related with mating and ovipositional activities. The aim of this research is to determine the reproductive profile and its manure of the Black Soldier Fly (Hermetia Illucens L.) through different rearing substrate as ruminant feed. A total of 4 treatments and 4 replicates were used in this experiment. The treatment diet was formulated as follows:    T0:  dry fermented cow waste, T1: 21% of crude protein, T2: 22% of protein, T3: 23% of protein. The data was analyzed using ODA SAS on an academic general linear model (GLM).  The result showed using different rearing substrates gave insignificant differences (p > 0.05) on the reproductive profile, nutritional content, and manure nutritional content. In summary, the use of different leves of protein can be used as the rearing substrate without any adverse effects.